A population study of urine glycerol concentrations in elite athletes competing in North America. Issue 11 (24th September 2013) - Kelly, Brian N.; Madsen, Myke; Sharpe, Ken; Nair, Vinod; Eichner, Daniel
Abstract : Glycerol is an endogenous substance that is on the World Anti‐Doping Agency's list of prohibited threshold substances due to its potential use as a plasma volume expansion agent. The WADA has set the threshold for urine glycerol, including measurement uncertainty, at 1.3 mg/mL. Glycerol in circulation largely comes from metabolism of triglycerides in order to meet energy requirements and when the renal threshold is eclipsed, glycerol is excreted into urine. In part due to ethnic differences in postprandial triglyceride concentrations, we investigated urine glycerol concentrations in a population of elite athletes competing in North America and compared the results to those of athletes competing in Europe. 959 urine samples from elite athletes competing in North America collected for anti‐doping purposes were analyzed for urine glycerol concentrations by a gas chromatography mass‐spectrometry method. Samples were divided into groups according to: Timing (in‐ or out‐of‐competition), Class (strength, game, or endurance sports) and Gender. 333 (34.7%) samples had undetectable amounts of glycerol (<1 μg/mL). 861 (89.8%) of the samples had glycerol concentrations ≤20 μg/mL. The highest glycerol concentration observed was 652 μg/mL. Analysis of the data finds the effects of each category to be statistically significant. The largest estimate of the 99.9 th percentile, from the in‐competition, female, strength athlete samples, was 1813 μg/mL with a 95% confidence range from 774 to 4251 μg/mL. This suggests a conservative threshold of 4.3 mg/mL, which would result in a reasonable detection window for urine samples collected in‐competition for all genders and sport classes. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Glycerol is a naturally occurring, prohibited substance potentially used by athletes in an effort to mask blood manipulation. Due to its endogenous nature, it is necessary to determine the threshold above which no athlete should naturally have a glycerol concentration in their urine. Data from a population (n = 959) study of urine glycerol concentrations present in anti‐doping control samples collected from elite athletes competing in North America in various disciplines as well as competition status are presented in this manuscript.